Valiron-type and valiron-titchmarsh-type theorems for entire functions of order zero - Zabolotskii, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
By using known asymptotics of the counting function of zeros of an entire function f of order zero, we determine the asymptotics of In f under the condition that all zeros off lie on the same ray. The inverse problem is also analyzed.